e-CAFE @ Petaling Jaya / Amir Haziq Hamdan ... [et al.] - Hamdan, Amir Haziq; Mohd Nizam, Muhammad Amirullah; Mohd Nor Azhar, Muhammad Danial Imran; Abdul Rasam, Abdul Rauf (College of Built Environment, 2023)
The idea for this project is to create a map that describe the top cafes that have been reviewed by customers on many websites can be found and we classified them by their rating so the user can use the map as a reference to choose which cafes are suitable to their taste the most.